Endoscopic Ossiculoplasty - Sandrine Machiels; Jolien Euben; Nicolas Mardyla (B-ENT)
Endoscopic ear surgery is evolving as a treatment modality for temporal bone pathologies.We wish to discuss the advantages and difficulties of the use of the endoscope to assess and address ossicular chain pathology.